PARTISIPASI PETANI DALAM KEGIATAN DAFEP DI KABUPATEN BANTUL (FARMER'S PARTICIPATION IN DAFEP PROJECT) - Husodo, Sapto (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2006)
This research aims to know farmer's participation in DAFEP Project and to identify factors influencing it. The data were collected through a survey for farmers who participate in DAFEP Project in Bantul Regency organized since October 2005 until January 2006. To measure farmer's participation used score followed by proportional test. To determine factors influencing farmer's participation used regression model with one dependent variable namely farmer's participation in DAFEP Project and eight independent variables. Results suggest that farmer's participation in DAFEP Project in Bantul Regency was relatively high which reached at about 97 %. Results also indicate that farmer's participation in DAFEP Project was affected by age, horizon, attitude, motivation, extension intensity, dynamic group, and the role of society leaders.